Intolerance of uncertainty over COVID-19 pandemic and its effect on anxiety and depressive symptoms - del Valle, Macarena Verónica; Andrés, María Laura; Urquijo, Sebastián; Yerro-Avincetto, Matías; López-Morales, Hernán; Canet-Juric, Lorena (Revista Interamericana de Psicología/Interamerican Journal of Psychology, 2020)
As the COVID-19 pandemic represents an unprecedented uncertain situation, the aim of this study is to determine the effect of intolerance of uncertainty over COVID-19 pandemic on anxiety and depressive symptoms during the quarantine. The study was conducted with 3805 Argentinean participants, who fulfilled the Beck Depression Inventory, the State-Trait Anxiety Inventory, and a modified version of the Intolerance of Uncertainty Scale. Regression analyses indicated a significant effect of intolerance of uncertainty on anxiety and on depressive symptoms. A minor effect of age and gender was also found. Young women with greater intolerance of uncertainty showed the highest levels of anxiety and depressive symptoms. Even though uncertainty distress is an understandable reaction to the current situation, these psychological effects should be monitored.